O-033 Jugular Vein Flow Patterns in Patients with Pulsatile Tinnitus Using Computational Fluid Dynamics. (29th July 2016) - Kao, E; Kefayati, S; Meisel, K; Ballweber, M; Faraji, F; Halbach, V; Saloner, D; Amans, M
Abstract : Introduction/purpose: Aberrations of venous anatomy can cause pulsatile tinnitus (PT). However, venous anatomy variation in patients without pulsatile tinnitus (PT) is extremely variable. Conventional imaging modalities, including cerebral angiography, provide little insight into the complex flow patterns in the cerebral veins. The aim of this study was to use subject-specific contrast-enhanced MRA (CE-MRA) determined anatomy, and MRV-based inlet flow conditions to develop computational fluid dynamics (CFD) models of flow in subjects with suspected venous pulsatile tinnitus and subjects without pulsatile tinnitus to investigate how the geometry of the jugular vein affects flow. Materials and methods: 7 jugular veins (4 normal, 3 with pulsatile tinnitus) were imaged with CE-MRA. 2 D phase contrast MRV was also acquired transverse to the sigmoid sinus to determine inlet flow conditions. Surfaces were segmented using VMTK (Orobix, Bergamo, Italy) and Geomagic Design X (Geomagic, Rock Hill, USA). Tetrahedral meshing was also performed in VMTK, using a target edge-length of 0.6 mm. CFD simulations were performed in FLUENT (ANSYS, Canonsburg, USA), using flow values obtained from the literature and in vivo measurements.Flow patterns in the jugular vein were characterized by their vortex core-lines, which were extracted from simulation data using Ensight (CEI, Apex, USA). Additional flow-parameters were calculated in MATLAB (Mathworks, Natick, USA) and pathlines visualized using Paraview (Kitware, New York, USA). Results: Patients with suspected venous PT had flow distinct patterns from those in normal subjects. Non-PT flow was characterized by organized redirection of flow from the sigmoid sinus along the curvature of the bulb into the jugular vein (A) with vortex cores in the jugular bulb (C). PT flow was characterized by larger helical flow structures throughout the proximal jugular vein created by flow directed perpendicular to the sigmoid sinus flow (B) and vortex cores that were more diffusely organized (D). High flow rates, and even turbulence, were noted in the proximal jugular vein – near the level of the carotid bifurcation – where there was often pronounced narrowing of the jugular. Conclusion: The geometry of the jugular vein significantly affects the position, size, and length of the vortex cores. Our results suggest a link between geometry, flow, and PT. Disclosures: E. Kao: None. S. Kefayati: None. K. Meisel: None. M. Ballweber: None. F. Faraji: None. V. Halbach: None. D. Saloner: None. M. Amans: None.